Cost-effectiveness of anti-tumour necrosis factor drugs for the treatment of rheumatoid arthritis in Ireland - Adams, Roisin C. (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Pharmacology & Therapeutics, 2012)
Rheumatoid Arthritis (RA) is the most common form of inflammatory arthritis. It is a chronic condition that places a substantial burden on patients and their carers, imposing a negative effect on quality of life (QOL), including physical, psychological, and social functioning and is associated with premature mortality. Treatment pathways include disease modifying agents (DMARDs) followed by anti- TNF therapy if poor or loss of response is evident. In 2009, expenditure for anti-TNF drugs reached approximately €100 million. All of the anti-TNF agents are used and reimbursed either under the community drugs schemes, or by hospitals. These include adalimumab, certolizumab, etanercept, golimumab, and infliximab. This thesis examines the cost-effectiveness of anti-TNF agents for treatment of RA in the Irish healthcare setting. Two of these agents have undergone pharmacoeconomic assessment and were initially refused reimbursement due to uncertainty associated with their cost-effectiveness. In order to assess the cost effectiveness of these agents in the Irish setting an economic evaluation was performed.
Keywords: Pharmacology & Therapeutics, Ph.D.; Ph.D. Trinity College Dublin